Knowledge Relationships Mother With Temper Tantrum Behavior In Children In Puskesmas Payung Sekaki Pekanbaru 2019: Knowledge Relationships Mother With Temper Tantrum Behavior In Children In Puskesmas Payung Sekaki Pekanbaru 2019 - Berliana Irianti (Institute Of Computer Science (IOCS), 2020)
Knowledge is what is known by the person or respondents with respect to healthy and sick or health. Temper tantrums are an outburst of explosive and uncontrolled. Temper tantrums often occur in children aged 15 months to 6 years. Children's early period was the golden era for parents, children's early period is a difficult time for most of the child's personality development fraught with difficulties and children are often demanding freedom despite their liberty still fail to obtain. This study aims to determine the